Advances in enzymology and related Areas of molecular biology : (Interscience Publishers, 2004)
The Advances in Enzymology and Related Areas of Molecular Biology series is one of the most prestigous in the field, devoted to the latest trends in molecular biology and enzymology. Each volume of the series contains contributions from leading authorities in the field. This volume contains the cumulative subject indices for Volume 1-74 in the series, making it an invaluable tool for researchers in the field.